Distinct Pathogenesis of Pancreatic Cancer Microvesicle–Associated Venous Thrombosis Identifies New Antithrombotic Targets In Vivo. Issue 4 (April 2018) - Stark, Konstantin; Schubert, Irene; Joshi, Urjita; Kilani, Badr; Hoseinpour, Parandis; Thakur, Manovriti; Grünauer, Petra; Pfeiler, Susanne; Schmidergall, Tobias; Stockhausen, Sven; Bäumer, Markus; Chandraratne, Sue; et al.
Abstract : Objective—: Cancer patients are at high risk of developing deep venous thrombosis (DVT) and venous thromboembolism, a leading cause of mortality in this population. However, it is largely unclear how malignant tumors drive the prothrombotic cascade culminating in DVT. Approach and Results—: Here, we addressed the pathophysiology of malignant DVT compared with nonmalignant DVT and focused on the role of tumor microvesicles as potential targets to prevent cancer-associated DVT. We show that microvesicles released by pancreatic adenocarcinoma cells (pancreatic tumor–derived microvesicles [pcMV]) boost thrombus formation in a model of flow restriction of the mouse vena cava. This depends on the synergistic activation of coagulation by pcMV and host tissue factor. Unlike nonmalignant DVT, which is initiated and propagated by innate immune cells, thrombosis triggered by pcMV was largely independent of myeloid leukocytes or platelets. Instead, we identified externalization of the phospholipid phosphatidylethanolamine as a major mechanism controlling the prothrombotic activity of pcMV. Disrupting phosphatidylethanolamine-dependent activation of factor X suppressed pcMV-induced DVT without causing changes in hemostasis. Conclusions—: Together, we show here that the pathophysiology of pcMV-associated experimental DVT differs markedly from innate immune cell–promoted nonmalignant DVT and is therefore amenable to distinct antithrombotic strategies. Targeting phosphatidylethanolamine on tumor microvesicles could be a new strategy for prevention of cancer-associated DVT without causing bleeding complications. Abstract : Supplemental Digital Content is available in the text.